Ulrike Felsing: Reflexive Exhibition Catalogues (KULT_online, 2023)
The dissertation Reflexive Ausstellungskataloge — Ein Medium der Übersetzung als Ausstellung, Film und Hypertext deals with intermedial references in the design of exhibition catalogues. Using five examples, Ulrike Felsing traces design techniques that dynamically relate a) the exhibited artwork(s), b) the spatiality of the presentation as well as the curatorial practice of the installation and c) the mediality of the (printed) book to one another.